Retained Descemet’s membrane following penetrating keratoplasty for Fuchs’ endothelial dystrophy: a case report of a post-operative complication - McVeigh K (Dove Medical Press, 2013)
Katherine McVeigh,1,3,* Kurt Spiteri Cornish,3 Aravind R Reddy,3 Georgios Vakros2,3,* 1Eye Clinic, Royal United Bath Hospital, Bath, UK; 2Birmingham Midland Eye Centre, Birmingham City Hospital, Birmingham, UK; 3Ophthalmology Department, Aberdeen Royal Infirmary, Aberdeen, United Kingdom *These authors have contributed equally Purpose: To report a case of retained Descemet’s membrane following penetrating keratoplasty in a patient suffering from Fuchs’ endothelial corneal dystrophy. The use of confocal microscopy, histopathological tissue analysis, and treatment options are discussed. Methods: Case report of an 85-year-old man with a past ophthalmic history of atrophic macular degeneration, underwent a penetrating keratoplasty for Fuchs’ endothelial corneal dystrophy. Postoperative review revealed a retained retrocorneal membrane within the anterior chamber. Further surgery was performed to excise the membrane, with a subjective and objective postoperative improvement in visual acuity and without subsequent complications of the corneal graft. Results: Histopathological assessment confirmed the clinical suspicion of a retained Descemet’s membrane, marrying with the initial histology from the corneal button excised during the penetrating keratoplasty, which showed only a very thin Descemet’s layer. Conclusion: Retention of the Descemet’s membrane following penetrating keratoplasty is a rare but potential complication of this surgery, particularly in cases of Fuchs’ endothelial corneal dystrophy due to the thickened and abnormal histological nature of the endothelium and high index of suspicion is required. Keywords: retained Descemet’s membrane, penetrating keratoplasty, Fuch’s endothelial corneal dystrophy, corneal graft